Seasonal variation in incidence and relapse of granulomatosis with polyangiitis: A retrospective cohort study from Central Anatolia - Soytürk, Gülşah; Konak, Hatice Ecem; Dağlı, Pınar Akyüz; Ulucaköy, Rezan Koçak; Atalar, Ebru; Erdoğan, Esra Kayacan; Babaoğlu, Hakan; Armağan, Berkan; Orhan, Kevser; Maraş, Yüksel; Erten, Şükran; Küçükşahin, Orhan; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: The etiology of granulomatosis with polyangiitis (GPA) remains under discussion. This study aims to explore patterns of organ involvement, ANCA antibody profiles, seasonal attack rates, and their interrelationship among patients diagnosed with ANCA-associated vasculitis (AAV) in Central Anatolia, shedding light on its multifactorial etiology involving drugs, genetics and environmental factors. Methods: We conducted a retrospective study involving patients aged 18 to 65 diagnosed with GPA and receiving care at Ankara Bilkent City Hospital Rheumatology Clinic. Diagnosis criteria followed the 2012 Chapel Hill Consensus Conference guidelines and the 2022 American College of Rheumatology/European Association of Rheumatology Societies classification for AAV. Patient data included demographics, antibody test results, seasons of diagnosis and flare, affected organs, and Birmingham Vasculitis Activity Score (BVAS). Organ involvement was determined based on biopsy findings or established criteria. Results: Our study included 75 patients, with the majority exhibiting cANCA-IFA positivity (94.7%) and PR3-ANCA ELISA positivity (98.3%). During follow-up, 70.7% experienced their first flare, with 37.7% experiencing a second flare. Lung involvement was most common at diagnosis and during flares, followed by ear-nose-throat and renal involvement. Seasonal analysis revealed peaks in disease onset in March, November, and April, with flares more common in September, May, October, and November. Autumn was the most common season for the first flare. Conclusions: This study provides novel insights into ANCA-associated vasculitis epidemiology in Central Anatolia. Our findings underscore the intricate seasonal variation and infectious triggers of GPA exacerbations, highlighting the importance of tailored management strategies to mitigate disease flares.